THE POTENTIAL OF PROCESSING BYPRODUCT OF SYRUP KALAMANSI TOWARD “ZERO WASTE” - Kurnia Herlina Dewi; Sigit Mujiharjo; Acep Pebrian Utama (BPFP Faperta UNIB, 2016)
Residual result from cyrup of calamansi was plenteous and did not used yet well. This research was used to utilize that residual industry of cyrup calamansi by cultivating it became essential oil by using distillation method. The residual result from cyrup of calamansi were devided into three types; residual result in solid, residual result in liquid 1, and residual result in liquid 2. From 100 kg fresh calamansi could produce 40 kg residual result in solid, 20 liters liquid 1 and 10 liters liquid 2. Each of them produced essential oil which 300,79 gr (from residual solid), 354,39 gr (from residual result of liquid 1) and 22,33 gr (from residual result of liquid 2). By looking at the yield, residual result industry of cyrup calamansi which contain the highest of essential oil was residual result from liquid 1 with the yield 1,771%, essential oil from the solid was 0,752% and the yield from the residual liquid was 0,223%. The essential oil from cyrup of calamansi was near to the characteristic of lime essential oil in density, refractive index and the yield but for solubility in alcohol was different.